Incorporating hydroacoustic signal classification technique for effective application to limits of acceptable change framework for natural heritage conservation at Pulau Payar Marine Park - Anisah Lee Abdullah; Juliana Mohamed; Zulfigar Yasin (Environmental Management Society, Malaysia, 2011)
With the coastal resources declination at an alarming rate, development of new techniques or combination of techniques is needed and inevitable to provide faster, more accurate and broader-scale applications for natural heritage conservation strategy. The integrated conservation strategy to conserve the coral reefs is a dynamic approach. In thie study a combination of twi approaches- limits of Acceptable Change framework and hydroacoustic technique, was applied to a coral reef area as a pilot study in adopting a science-based ecosystem approach to understanding a coral scosystems as a natural heritage conservation measure. The limits of Acceptable Change( LAC)framework, originally developed to help better manage increasing demands and impacts by hikers and backpackers in U.S wilderness system was applied to Pulau Payar Marine park as apilot project. This was because LAC seems to have the broadest applicability to the complex tourism setting of the marine parks. The planning procedure consist of a series of interrelated steps leading to the development of the set of measurable objectives that defines the desired wilderness conditions.It also identifies the management actions necessary to maintain or archive those conditions Similar situation is also faced by Pulau Payar marinepark managers on how to provide for overall quality enjoyment of increasingly large numbers of visitors while preserving the fragile ecisystems within the narine park, particularly the coral reefs. In order to apply LAC, coral reef survey will be done to determine current coral reef percentage. For this purpose, a hydroacoustic technique using Hydroacoustic Signal Processing System (RoxAnn), was chosen to be incorporated to LAC framework as RoxAnn has been proven to be a succesful large scale survey tool capable of mapping a wide variety of sea-bed types.The use of hyroacoustic Signal signals as a remotesensing tool is capable of determining the distribution of coral habitats and categories within the coral reef by measuring different hardness and roughness of the substrate. The system stories categories and manipulates data received and produces maps of the sea-bed types especially corals. This technique will help to determine the percentage of coral reef (e.g:live and dead coral) and in the inventory process of applying LAC for a large scale survey.This pilot study has proven that the combination of technique i.e.the applicationof LAC framework and hydroacoustic signal processing is a viable, cost-effective and time-saving method to conduct a science-based ecosystem approach to further understand the coral reefs as our natural heritage.